INDIAN MOBILE BANKING IN POST COVID-19: AN ANALYTICAL STUDY AND GRATIFICATION FROM THE ASPECT OF KANO MODEL - Jaywant, Bhadane; Nayan, Rajiv; Bhau, Gaikar Vilas; Singh, Kanwal Jeet; Bharat, Joshi (Indian Journal of Finance and Banking, 2023)
The purpose of the present research paper is to understand the research questions related to M-banking. It is the time call to take up Virtual Banking (VB) with Zero Contact Banking (ZCB) as a preventive measure to COVID-19. The study also admits the comparative analysis on the gratification of M-banking users considering factors/attributes of the Kano Model. The researcher has undertaken Integrative Approach (IA) for both, related to literature reviewed and survey so far observed. Both primary data through well-structured questionnaires from 900 M-banking users of SBI, HDFC, and Citi Bank (300 from each) and secondary data from published sources have been cantered and cited to understand the syntactic research gap. The researcher has followed Stratified Random Sampling for sample banks considering the date of establishment, volume and value of M-banking transactions, number of employees, and Convenient Random Sampling for M-banking users, to make the sample representative. The objectives were studied thoroughly and hypotheses were tested in SPSS. The researcher has used Kolmogorov-Smirnov (D-Statistic) and Shapiro-Wilk test (W-Statistic) to test data normality, Cronbachs’ Alpha to test Data Reliability, Descriptive Statistics i.e. frequency and per cent count to describe data and Chi-square to measure significant associations and differences if any. The researcher has drawn an epilogue purely on the basis of data collection and analysis. The researcher has conducted Pearson’s Product Movement Correlation, to suggest a correlation on Y-intercept Model to show an association between volume and value of M-banking transactions of SBI, HDFC, and Citi Bank and suggested a model fit to regression equation. This paper gives a unique insight into KANO model. JEL Classification Codes: A1, A30, C1, G17, Y8.